The external productivity of the business administration program of Siena College, Quezon City, 1988 to 1990 - Garcia, Libertad P. (Animo Repository, 1994)
This is an assessment of the external productivity of the Business Administration (BA) program of Siena College, Quezon City from SY 1988 to 1990 with reference to the employment of the graduates of the program. The study employed the descriptive-correlational method of research. It presented and analyzed the external productivity of the program based on the information gathered from the (1) BA graduates of SY 1988 to 1990 and (2) their immediate supervisors/heads. The study, likewise, determined which of the selected alumni-related and school-related factors significantly related with the external productivity of the program. The relationship between measures of external productivity and measures of internal efficiency of the program were determined using multiple correlation and stepwise regression. Two sets of questionnaires were developed by the researcher for data-gathering purposes. There was one set for the BA graduates as well as one set for the Ss' immediate supervisors/heads. Prior to actual use, the questionnaires were pilot-tested among 13 graduates of the program from batches 1980 to 1992. Prior to actual use, the instruments were further subjected to content validation by the experts. The BA program was internally efficient and externally productive. The external productivity of the program was dependent on faculty competence, relevance of the curriculum, and age of the graduates. The more competent the faculty members were, the more externally productive the BA program was expected to be. Furthermore, the more relevant the BA curriculum was, the greater the external productivity of the BA program tended to be. Because age, faculty competence, and relevance of the curriculum could explain only 22.82 percent of the variance in the external productivity of the BA program, there were other factors which were not covered in the investigation. This could account for the remaining variance in the dependent variable. Owing to their actual job experiences in the field, the BA graduates were valuable sources of feedback on specific areas that needed to be improved in the BA program of the respondent school.